The transformational qualities of dramatic arts (2014)
ABSTARCT: During the International Drama and Education Association (IDEA) Congress in Kenya in 1998, the life of two educators crossed roads. Although both are from different geographical contexts (Colombia and the United States), they have shared the same passion: to encourage in their societies the implementation of dramatic arts in different educational settings (schools, universities, communities) so children and adults could develop to their fullest, thus enabling them to participate actively in building a more democratic society. Fifteen years after this encounter, they met again in the 2013 IDEA Congress in Paris to reflect on their efforts during their life spans. Through examining their drama practices, they discuss how this human expression functions as a critical thinking art form, changing players, audiences, and communities. Lessons derived from their experiences might be useful for a new generation of transformational drama leaders.